Methanol extract of Melastoma malabathricum leaves exerted antioxidant and liver protective activity in rats - Mamat, Siti Syariah; Kamarolzaman, Mohammad Fauzi Fahmi; Yahya, Farhana; Mahmood, Nur Diyana; Shahril, Mohamad Syahmi; Jakius, Krystal Fredolin; Mohtaruddin, Norhafizah; Darnis, Deny Susanti; Bakhtiar, M. Taher; Zakaria, Zainul Amiruddin (BioMed Central, 2013)
Background Melastoma malabathricum L. (Melastomaceae) is a small shrub with various medicinal uses. The present study was carried out to determine the hepatoprotective activity of methanol extract of M. malabathricum leaves (MEMM) against the paracetamol-induced liver toxicity in rats model. Methods The respective chemicals and herbal solutions (10% DMSO, 200 mg/kg silymarin or MEMM (50, 250 and 500 mg/kg)) were administered orally to rats once everyday for 7 days followed by the hepatotoxicity assay. The blood samples and livers were collected and subjected to biochemical and microscopical analysis. Prior to the hepatoprotective study, MEMM was subjected to determination of the total phenolic content (TPC) and the antioxidant properties using several standard assays (e.g. 2, 2-diphenyl-1-picrylhydrazyl- and superoxide anion- radical scavenging assay, and oxygen radical absorbance capacity assay). Results MEMM exerted significant (p < 0.05) and high antioxidant activity in which high TPC was recorded; while in the hepatotoxicity study, the extract exhibited significant hepatoprotective effects against the paracetamol-induced hepatotoxic model. The results observed for serum liver enzymes (ALT, ALP and AST) as well as the microscopic observations and microscopic scoring supported the hepatoprotective potential of MEMM. The phytochemical and HPLC analysis of MEMM demonstrated the presence of flavonoids as its major constituents. Conclusions The MEMM-induced hepatoprotective activity could be allied partly to its antioxidant activity and the presence of flavonoids.